Flexible gel polymer electrolyte based on ionic liquid EMIMTFSI for rechargeable battery application. (10th March 2017) - Balo, Liton; Shalu,; Gupta, Himani; Kumar Singh, Varun; Kumar Singh, Rajendra
Graphical abstract: Schematic diagram and cyclic performance of flexible Li polymer battery based on prepared gel polymer electrolytes. Highlights: Gel polymer electrolytes containing ionic liquid EMIMTFSI were fabricate. Prepared electrolytes showed high ionic conductivity. They also showed high thermal and electrochemical stability. Fabricated lithium polymer batteries showed good electrochemical performance. Abstract: Development of high performance lithium polymer batteries (LPBs) with high thermal and electrochemical stabilities is now being intensively pursued for various applications like personal electronics, grid storage etc. In the present study, we report synthesis and characterization of a gel polymer electrolyte (GPE) based on polymer polyethylene oxide (PEO), salt lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) and different amounts of added ionic liquid (IL) 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (EMIMTFSI). Differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), complex impedance spectroscopy, ionic transference number studies, linear sweep voltammetry (LSV) and cyclic voltammetry (CV) studies exhibit promising characteristics of prepared GPEs for suitable application in LPBs. The GPEs show high thermal stability (i.e. no weight loss up to 310 °C), high ionic conductivity (∼2.08 × 10 −4  S cm −1 at 30 °C), high lithium transference number ( t Li +  = 0.39) and high electrochemical stability window (∼4.6 V). A low cost simple thermal lamination technique was used to encapsulate whole LPB assembly by sandwiching best performing GPE between a LiMn2 O4 cathode and lithium metal anode. In galvanostatic charge/discharge cycles the prepared cell showed good electrochemical performance.